Competitive Goals and Plant Investment in Environment and Safety Practices: Moderating Effect of National Culture. Issue 1 (February 2015) - Power, Damien; Klassen, Robert; Kull, Thomas J.; Simpson, Dayna
ABSTRACT Operations managers clearly play a critical role in targeting plant‐level investments toward environment and safety practices. In principle, a "rational" response would be to align this investment with senior management's competitive goals for operational performance. However, operations managers also are influenced by contingent factors, such as their national culture, thus creating potential tension that might bias investment away from a simple rational response. Using data from 1, 453 plants in 24 countries, we test the moderating influence of seven of the national cultural characteristics on investment at the plant level in environment and safety practices. Four of the seven national cultural characteristics from GLOBE (i.e., uncertainty avoidance, in‐group collectivism, future orientation and performance orientation) shifted investment away from an expected "rational" response. Positive bias was evident when the national culture favored consistency and formalized procedures and rewarded performance improvement. In contrast, managers exhibited negative bias when familial groups and local coalitions were powerful, or future outcomes—rather than current actions—were more important. Overall, this study highlights the critical importance of moving beyond a naïve expectation that plant‐level investment will naturally align with corporate competitive goals for environment and safety. Instead, the national culture where the plant is located will influence these investments, and must be taken into account by senior management.